Discourse on Neocolonialism as an Element of Russia’s Foreign Policy Identity in Africa - A. R. Shishkina; E. D. Fain; L. M. Issaev (Международная аналитика)
This article addresses the issue of neocolonialism and, in particular, the context in which this issue is addressed within the framework of Russian oﬃcial foreign policy. The article gives an idea of the emergence and modern understanding of the concept of neocolonialism within the framework of political science. The authors use the method of content analysis of speeches, statements and articles by Russian oﬃcials that contain references to neo-colonialism and the fight against it on the African continent. It is shown that the narrative of neocolonialism occupies a fairly important place in the Russian Federation’s construction of its foreign policy identity as a form of building a discursive dialogue with Western countries. The peculiarities of the Russian discourse on neocolonialism are its focus on problems in the spheres of economics and security, as well as some abstractness in relation to specific forms and manifestations of neocolonialism in African countries.